2018
DOI: 10.1016/j.euroneuro.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral-mediated let-7d microRNA overexpression induced anxiolytic- and anti-depressant-like behaviors and impaired dopamine D3 receptor expression

Abstract: Generalized anxiety and major depression disorders (MDD) are severe debilitating mood disorders whose etiology are not fully understood, but growing evidence indicates that microRNAs (miRNAs) might play a key role in their neuropathophysiological mechanisms. In the current study, we investigate the role of Lethal-7 (let-7d) miRNA, and its direct target dopamine D3 receptor (D3R) gain-of-function, in the hippocampus, in preclinical models of anxiety and depression in mice. For this purpose, we have constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
(56 reference statements)
2
15
0
Order By: Relevance
“…It is well-established that, via D3R, DA is a central modulator of accumbal activity that plays critical roles in many drugs of abuse including alcohol. We have shown in a previous study that, like the D3R agonist 7-OH-DPAT, D3R overexpression exacerbated alcohol intake ( Bahi and Dreyer, 2018 ). In contrast, like the D3R selective antagonist SB-277011-A, D3R knockdown using lentiviral-mediated siRNA expression, attenuated voluntary alcohol consumption ( Bahi and Dreyer, 2014 ), which agrees with other findings using SB-277011-A in C57BL/J6 mice ( Rice et al, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is well-established that, via D3R, DA is a central modulator of accumbal activity that plays critical roles in many drugs of abuse including alcohol. We have shown in a previous study that, like the D3R agonist 7-OH-DPAT, D3R overexpression exacerbated alcohol intake ( Bahi and Dreyer, 2018 ). In contrast, like the D3R selective antagonist SB-277011-A, D3R knockdown using lentiviral-mediated siRNA expression, attenuated voluntary alcohol consumption ( Bahi and Dreyer, 2014 ), which agrees with other findings using SB-277011-A in C57BL/J6 mice ( Rice et al, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…In order to determine the potential role of let-7d in voluntary alcohol intake and preference, the effect of let-7d on the expression of accumbal D3R mRNA in rat was determined. Both gain-of-function and loss-of-function approaches have demonstrated that let-7d was a strong regulator for the expression of D3R ( Bahi and Dreyer, 2018 ). Therefore, and as expected, it has been found that D3R mRNA expression was significantly inhibited by overexpression of let-7d These findings are in line with previous studies from our laboratory, using computational examination and experimental approach, which have demonstrated that D3R might be a direct target gene of let-7d ( Chandrasekar and Dreyer, 2009 ;.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Growing evidence indicates that let-7d may play a role in the neurobiology of psychiatric disorders [ 68 ]. Let-7d is largely expressed in the brain and is involved in modulating learning and memory [ 69 , 70 ]; however, little is known about its role in stress-related disorders. Interestingly, its upregulation was reported in the nucleus accumbens in a cocaine-conditioned place preference rat model and, in its circulating form, in animals that had undergone chronic social defeat [ 52 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both receptors, DRD1 and DRD2, are associated with control of food intake, either homeostatic or hedonic, in several areas of the brain ( Wise, 1989 ; Ikeda et al, 2018 ) which indicates that its modulation through miRNAs can modulate the food intake. In addition, overexpression of let-7d is negatively correlated with the expression of DRD3 in the hippocampus of mice ( Bahi and Dreyer, 2018 ). The activity of the DRD3 is controversy in the context of food intake, but some evidences associate it with eating disorders and decreased food intake ( Thomsen et al, 2017 ; González et al, 2019 ).…”
Section: Dopamine: Role On Feeding Behavior Influences Of Els and Mmentioning
confidence: 99%